One charmed Christmas - Roberts, Sheila, 1951- (Mira, 2020)
"Catherine Pine is hoping her Christmas is a bit more jolly than last year's. That one was her first without her husband, and with her kids and their families absent this year, she's worried. But things change when her good friend invites her on a Christmas cruise to lift her spirits. Suddenly every day is an adventure and she's making a bunch of new friends, including the lovable Sophie Miles. It's like a gift from Santa when Sophie and Catherine meet the charming Dr. Rudy Nichols, a perfect match for hypochondriac Sophie. But he comes with a two-legged lump of coal, his guard-dog daughter. And then there's chocolatier Trevor March, who's also interested in the scrumptious Sophie. Can he convince her that chocolate is the perfect cure for what ails her? Who knows what Santa has in store for these holiday travelers?"--